The spellshop - Durst, Sarah Beth (Bramble, Tor Publishing Group, 2024)
"Kiela has always had trouble dealing with people. Thankfully, as librarian at the Great Library of Alyssium, she and her assistant Caz--a magically sentient spider plant--have spent the last decade sequestered among the empire's most precious spellbooks, preserving their magic for the city's elite. Then a revolution begins and the library goes up in flames. She and Caz flee with all the spellbooks they can carry and head to a remote island Kiela never thought she'd see again: her childhood home. Taking refuge there, Kiela discovers, much to her dismay, a nosy--and very handsome--neighbor who can't take a hint and keeps showing up day after day to make sure she's fed and help fix up her new home. In need of income and reluctantly inspired by the beauty and people of the island who have welcomed her into their hearts, Kiela discovers something that even the bakery in town doesn't have: jam. With the help of an old recipe book her parents left her and a bit of illegal magic, her cottage garden is soon covered in ripe berries that become the town's, and her handsome neighbor's, new favorite confection. But magic can do more than make life a little sweeter, so Kiela decides to open the island's first-ever and much-needed secret spellshop. Her plan comes with risks--the empire condemns the use of unsanctioned magic, and the consequence of sharing spells with commoners is death. But Kiela has only just found a place that feels like home and people who feel like family, and she'll risk anything for a chance at happiness."--